Natural products for managing landscape and garden pests in Florida - Matthew A. Borden; Eileen A. Buss; Sydney G. Park Brown; Adam G. Dale (EDIS)
Many people are seeking available and effective options that are safer for people and the environment than some conventional synthetic pesticides. There is also rising interest in organic gardening, which relies on many natural pesticides. Natural products can be used in isolation or combination with conventional pesticide programs as valuable rotation options, delaying or preventing onset of insect and disease resistance caused by repeatedly using the same chemical controls. This publication describes natural products used in residential landscapes and gardens that are generally less toxic to non-target organisms and the environment, and when used correctly, can be effective tools for plant protection. These products are most effective when used in an integrated pest management (IPM) program along with sanitation, proper cultural or maintenance practices, mechanical control tactics, use of resistant plant varieties, and biological control, when possible.